Vaccinations against COVID-19 in the opinion of medical services workers and the general social opinion - Rafa, Elżbieta; Majoch, Monika; Siekierczak, Sylwia; Węgrzyn, Izabella; Wenecka-Lipka, Beata (Journal of Education, Health and Sport, 2023)
Introduction This study was devoted to getting to know the public opinion, including representatives of medical professions, regarding the presented views on vaccination against Covid-19, allowing to determine the most important issues related to the lack of acceptance of this preparation. Aim The aim of this study was to find out the social opinion regarding vaccination against Covid-19 (including the aspect of vaccination obligation, incidence of adverse post-vaccination reactions, vaccination among children and pregnant women) as well as the reasons for the attitude towards the fact of accepting the vaccine or rejecting the possibility of being vaccinated. Material and methods The study was conducted in a group of 510 people - practicing the medical profession and not related to the health service, who were over 18 years old. The method of a diagnostic survey was used with the use of a proprietary questionnaire containing single and multiple choice questions, the survey was conducted on-line using a Google form in October 2022. Results In the study group, the vaccination rate was 62.2%, women and medical professionals were more likely to be vaccinated. The decision to be vaccinated was mainly based on the desire to protect themselves against the severe course of a possible illness - 30.4% of respondents and to protect themselves and others against Covid-19 - 26.5%. In the represented group, unvaccinated persons accounted for 37.8% respectively, they did not decide to vaccinate mainly because of the belief that they were not protected against the disease - 19.8% of respondents, perceiving COVID-19 as a seasonal infection - 19.0%, and fear of long-term complications - 18.6%. The decision to vaccinate was accompanied by i.a. feelings such as: slight fear (36.3%), fear/anxiety (10.4%), strong fear/anxiety (3.7%). The study group was also asked about adverse post-vaccination reactions, 25.1% of the surveyed experienced complications, most of them did not report adverse post-vaccination reactions, and the percentage of reported cases was 1.6%. The vast majority of respondents - 74.5% were in favor of the lack of obligation to vaccinate. Opinions expressed about the safety of vaccinations: rather yes - 24%, rather not - 22% and definitely not - 21%, a significant part had no opinion - 24.3%. Conclusions This study confirms the significant problem of skepticism towards Covid-19 vaccination, as well as the high percentage of people expressing opposition to the obligation to vaccinate and the perception of the media campaign as propaganda, which confirms the existence of a significant social division regarding the acceptance of vaccination. The perception of vaccine safety is related to the knowledge of adverse post-vaccination reactions, but the problem observed among respondents is the fact that the number of reported adverse reactions is negligible.